Il genere come dispositivo di soggettivazione. I "Dramolette" di Robert Walser e la voce della fiaba (Comparatismi, 2025)
The essay explores the possibility of interpreting literary genres as devices of subjectivation in Robert Walser’s Dramolette, specifically in the fairy-tale dramas Cinderella and Snow White, in order to highlight how literary genre is not merely a regulatory structure but also a dynamic means of creating and deconstructing the plots and subjectivities of both authors and fictional characters. The essay demonstrates how Walser manipulates the genres of fairy tale, classical drama, and comedy, intertwining them to question the concept of subjectivation: characters emerge as dynamic subjects, capable of rejecting the imposition of predefined genres. The article references the theories of the dispositif by Foucault and Deleuze, cross-referencing them with Bagni’s views on genre, to interpret literary genre as a system of dynamic and transformative forces.
Keywords: Walser; Literary genres; Dispositif; Cinderella; Snow White